Street to studio. - Schacter, Rafael (London : Lund Humphries, 2018)
Akay ; Argote, Ivan ; Ballard, Mike ; Behr, Clemens ; Downey, Brad ; Ekblad, Ida ; Eltono ; Faitakis, Stelios ; Falsnaes, Christian ; Herrero, Federico ; Huskmitnavn ; E.B. Itso ; James, Todd ; Kagami, Ken ; Katsu ; KAWS ; Kosta-Théfaine, Olivier ; Laric, Oliver ; McCarthy, Alicia ; McCarthy, Pat ; McGee, Barry ; Martinez, Eddie ; Maurice, Russell ; Minelli, Filippo ; Momo ; Muñoz, Daniel ; Neri, Ruby ; Nugroho, Eko ; Paredes, Sixe ; Payne, Oliver ; The Propeller Group ; Revok, Jason ; Roth, Evan ; Salvatus, Mark ; Sierra, Santiago ; Sortais, Ken ; Strange, Ian ; Swoon ; Tellegen, Boris ; Wermke/Leinkauf
boek